Decreased plasma l-arginine levels in organic acidurias (MMA and PA) and decreased plasma branched-chain amino acid levels in urea cycle disorders as a potential cause of growth retardation: options for treatment - Molema, Femke; Burgard, Peter; Kölker, Stefan; Hörster, Friederike; Posset, Roland (Molecular genetics and metabolism, 2019)
Background and aim - Patients with methylmalonic acidemia (MMA) and propionic acidemia (PA) and urea cycle disorders (UCD), treated with a protein restricted diet, are prone to growth failure. To obtain optimal growth and thereby efficacious protein incorporation, a diet containing the essential and functional amino acids for growth is necessary. Optimal growth will result in improved protein tolerance and possibly a decrease in the number of decompensations. It thus needs to be determined if amino acid deficiencies are associated with the growth retardation in these patient groups. We studied the correlations between plasma L-arginine levels, plasma branched chain amino acids (BCAA: L-isoleucine, L-leucine and L-valine) levels (amino acids known to influence growth), and height in MMA/PA and UCD patients. - Methods - We analyzed data from longitudinal visits made in stable metabolic periods by patients registered at the European Registry and Network for Intoxication Type Metabolic Diseases (E-IMD, Chafea no. 2010 12 01). - Results - In total, 263 MMA/PA and 311 UCD patients were included, all aged below 18years of age. In patients with MMA and PA, height z-score was positively associated with patients' natural-protein-to-energy prescription ratio and their plasma L-valine and L-arginine levels, while negatively associated with the amount of synthetic protein prescription and their age at visit. In all UCDs combined, height z-score was positively associated with the natural-protein-to-energy prescription ratio. In those with carbamylphosphate synthetase 1 deficiency (CPS1-D), those with male ornithine transcarbamylase deficiency (OTC-D), and those in the hyperornithinemia-hyperammonemia-homocitrullinuria (HHH) syndrome subgroup, height z-score was positively associated with patients' plasma L-leucine levels. In those with argininosuccinate synthetase deficiency (ASS-D) and argininosuccinate lyase deficiency (ASL-D), height was positively associated with patients' plasma L-valine levels. - Conclusion - Plasma L-arginine and L-valine levels in MMA/PA patients and plasma L-leucine and L-valine levels in UCD patients, as well as the protein-to-energy prescription ratio in both groups were positively associated with height. Optimization of these plasma amino acid levels is essential to support normal growth and increase protein tolerance in these disorders. Consequently this could improve the protein-to-energy intake ratio.
Gesehen am 04.12.2019